Improving Counselling Skills about Reproductive Health among Students by Using Peer Counselor Training - Ririn Harini; Ibrahim Rahmat; Wenny Artanty Nisman (Jurnal Ners, 2014)
Introduction: Nowadays, the goal of MDGs to improve maternal health is one of the priorities of many countries. Indonesian Government, by the National Family Planning Board (BKKBN), has followed up by monitoring and evaluating programs which is realized by providing technical guidance resilience in young people through Generation Planning program and developing Information and Consultation Center for Students Reproductive Health (PIK-KRM). In order to improve the role of peer counselors, a training should be done to increase their knowledge, attitudes, and skills. The objective of this research was to determine the effects of training on peer counselor’s knowledge, attitudes, and skills at PIK-KRM.Methods: The study was used quasy experiment pre-test and post-test nonequivalent control group design. Population were the committee of PIK-KRM at Faculty of Health, University of Muhammadiyah Malang, 80 students were included. Independent variable was training, while dependent variables were peer counselor’s knowledge, attitude, and skills. Data were collected by using questionnaire and observation form. Data were then analyzed by using paired t–test, independent sample t-test, simple linear regression.Results: The results of linear regression had showed that training have significant effect on peer counselor’s knowledge (p=0.000; R square=0.254), attitude (p=0.000; R square=0.432), and skills (p=0.000; R square=0.191).Discussion: Training can improve peer counselor’s knowledge, attitude, and skills at PIK-KRM board in giving information and counseling about reproductive health (sexuality, HIV/AIDS, and drugs). Nurses should provide continous training regularly, so their ability can be more better.